If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5 = x + 4 Reorder the terms: 5 + -1x = x + 4 Reorder the terms: 5 + -1x = 4 + x Solving 5 + -1x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + -1x + -1x = 4 + x + -1x Combine like terms: -1x + -1x = -2x 5 + -2x = 4 + x + -1x Combine like terms: x + -1x = 0 5 + -2x = 4 + 0 5 + -2x = 4 Add '-5' to each side of the equation. 5 + -5 + -2x = 4 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 4 + -5 -2x = 4 + -5 Combine like terms: 4 + -5 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5
| 4+35x=28x+8 | | 2y^2=9-4y | | 12+8q=15+7q | | 2(x+1)-3=3x-4 | | a=(12.5)(14.75) | | 72+2x+x=180 | | 2500+300=5000 | | -9-4x=-53x | | 6x-10=4x+4 | | 9y+3=5y+12 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4*0.4 | | 13-6x=5-7x | | 15x^2-19x=10 | | b+52=64 | | 6x+6=-54-4x | | 3(g+5)=36 | | (7-4i)(5+8i)= | | 12x+1=2x+3 | | 5g+g=12 | | 5+-2x=3x+1 | | 2(x+11)=0 | | 34=6-5x | | 19=9x+4-6x | | 5y+3(y-8)=5(y+1)-3 | | 2(x^2+6)+(2x-9)*2x= | | 3x-5-4x-3= | | 17=8x+5-4x | | 5+-1x=3x+1 | | 15-2*(-3x)=37 |